Приобретательная давность как способ приобретения права собственности - Netrusova, Yekaterina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the form of acquiring the ownership by prescription in the civil code of Russian Federation. Presenting that form the author focuses on the substantial dimension and integrity of the right to property and limitation of the ownership.